Valproic acid attenuates the suppression of acetyl histone H3 and CREB activity in an inducible cell model of Machado–Joseph disease. Issue 38 (25th July 2014) - Lin, X.P.; Feng, L.; Xie, C.G.; Chen, D.B.; Pei, Z.; Liang, X.L.; Xie, Q.Y.; Li, X.H.; Pan, S.Y.
Abstract: Machado–Joseph disease (MJD) is caused by a (CAG)n trinucleotide repeat expansion that is translated into an abnormally long polyglutamine tract. This disease is considered the most common form of spinocerebellar ataxia (SCA). In the present study, we developed stable inducible cell lines (PC12Tet‐On‐Ataxin‐3‐Q28/84) expressing ataxin‐3 with either normal or abnormal CAG repeats under doxycycline control. The expression of acetyl histone H3 and the induction of c‐Fos in response to cAMP were strongly suppressed in cells expressing the protein with the expanded polyglutamine tract. Treatment with valproic acid, a histone deacetylase inhibitor (HDACi), attenuated mutant ataxin‐3‐induced cell toxicity and suppression of acetyl histone H3, phosphorylated cAMP‐responsive element binding protein (p‐CREB) as well as c‐Fos expression. These results indicate that VPA can stimulate the up‐regulation of gene transcription through hyperacetylation. Thus, VPA might have a therapeutic effect on MJD.